2020
DOI: 10.2355/isijinternational.isijint-2019-502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Bulk Fe<sub>2</sub>O<sub>3</sub> Concentration on the Controlled Solidification of “Fe<sub>2</sub>O<sub>3</sub>”–CaO–SiO<sub>2</sub> Liquids in Air

Abstract: The solidification of "Fe 2 O 3 "-CaO-SiO 2 liquids in air at a controlled cooling rate of 2.0 K/s for a range of Fe 2 O 3 concentrations in the bulk has been investigated. The compositions investigated were selected such that the bulk compositions were within the hematite primary phase field and had a CaO/SiO 2 ratio of 3.46 wt/wt.Non-equilibrium phase assemblages were formed for all bulk compositions investigated. Specifically, the silico ferrite of calcium (SFC) phase was not formed on cooling. The microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 7 publications
4
12
0
Order By: Relevance
“…total pressure has been established in previous studies by the authors. 5) Systematic investigations of the controlled solidification of alumina-free "Fe 2 O 3 "-CaO-SiO 2 melts in air [6][7][8][9] have revealed unexpected observations. In particular, it has been shown that for a range of bulk compositions (Fe 2 O 3 concentrations and CaO/SiO 2 ratios) and cooling rates, the SFC phase does not form on cooling despite the fact that this phase is predicted to be thermodynamically stable under these conditions.…”
Section: Mechanisms Of Phase and Microstructure Formation During The Cooling Of "Fe 2 O 3 "-Cao-sio 2 -Al 2 O 3 Melts In Air And Implicatmentioning
confidence: 99%
See 4 more Smart Citations
“…total pressure has been established in previous studies by the authors. 5) Systematic investigations of the controlled solidification of alumina-free "Fe 2 O 3 "-CaO-SiO 2 melts in air [6][7][8][9] have revealed unexpected observations. In particular, it has been shown that for a range of bulk compositions (Fe 2 O 3 concentrations and CaO/SiO 2 ratios) and cooling rates, the SFC phase does not form on cooling despite the fact that this phase is predicted to be thermodynamically stable under these conditions.…”
Section: Mechanisms Of Phase and Microstructure Formation During The Cooling Of "Fe 2 O 3 "-Cao-sio 2 -Al 2 O 3 Melts In Air And Implicatmentioning
confidence: 99%
“…A necessary precondition for SFC and SFCA formation from the liquid is that, on cooling, the liquid composition passes through the SFC and SFCA primary phase fields; this is achieved primarily through control of the CaO/SiO 2 ratio of the bulk material. It has been shown, [6][7][8][9] however, that this on its own is not sufficient to guarantee the formation of the SFC phase. For example, in the "Fe 2 O 3 "-CaO-SiO 2 system in air, hematite, magnetite, dicalcium silicate, calcium diferrite and calcium ferrite phases, all having primary phase fields in this system, have been observed to form on cooling.…”
Section: Sfca Nucleationmentioning
confidence: 99%
See 3 more Smart Citations